Логаэд адоний: славянский ритмико-синтаксический инвариант - Preobrazhenski, Siergiej (Acta Polono-Ruthenica, 2018)
The article examines well-known (G. Derzhavin - J. Brodsky) and less known (G. Derzha- vin? C.K. Norwid? A. Mickiewicz? - J. Malaniuk) samples of the establishment of “heroic” aureole of logaoedic (adonic) verse, the possible Polish source of this aureole, and its early Polish “de-heroization” which has revealed the initial connotations and the general Slavonic source of the “alien” verseme (logaoed, truncated dactyl).